Assessing the effectiveness of a tri pramana oriented experiential learning model in enhancing critical thinking skills: a rasch analysis in primary science education - Ketut Susiani; Kadek Suranata; I Komang Gede Sukawijana; I Wayan Ardana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study evaluates the effectiveness of a Tri Pramana–oriented experiential learning model rooted in Balinese Hindu epistemology in enhancing critical thinking skills among 250 fourth-grade students in Natural and Social Sciences (IPAS). Using a post-test-only control group design, the intervention was implemented over six weeks in Bali, Indonesia, with experimental and control groups taught using culturally grounded experiential activities versus conventional instruction, respectively. Critical thinking was measured across five domains: identification, analysis, evaluation, inference, and communication. Data were analyzed using the Rasch measurement model via Winsteps software. Results showed high person reliability (0.80) and item reliability (0.95), with significant improvement in identification, analysis, and communication skills (mean logit = 0.49). However, evaluation and inference remained challenging for many students. The findings support the integration of culturally responsive, philosophy-based pedagogies in primary science education, while highlighting the need for targeted scaffolding in higher-order reasoning. Implications for curriculum developers and teachers include adapting local wisdom frameworks like Tri Pramana to foster 21st-century competencies through structured experiential tasks.